A comparison of a formal triage scoring system and a quick-look triage approach. (June 2016) - Betz, Martin; Stempien, James; Wilde, Alan; Bryce, Rhonda
Abstract : Background: Emergency Department (ED) triage systems have become increasingly comprehensive over time, requiring ever more resources such as nursing time and computer support. There are very few studies that have looked at whether this increased complexity results in improved performance. Objectives: This study looked at one aspect of performance, comparing reliability of triage nurses' (TNs) triage scores utilizing a simple quick-look method with a commonly used, resource-intense, five-level triage system. Methods: This observational study of TNs was carried out in two urban tertiary-care hospital EDs, in real time, assessing patients arriving consecutively. Immediately upon patients' arrival, TNs were asked to assign triage scores based simply on their observation of the patient and the chief complaint. The patient was then triaged in the department's usual way, utilizing a computer-assisted five-level triage system [Canadian Triage and Acuity Scale (CTAS)]. Agreement between scores was quantified. κ scores were calculated, and weighted by the CTAS score. Results: A total of 496 triage assessments were included. Percent agreement between the quick-look method and the standard CTAS method was 84.5%. κ scores were moderately high. Fourteen patients (2.6%), ultimately classified as CTAS 1 or 2, initially received lower scores from TNs using the quick-look method. No comparison of validity was assessed. Conclusion: TNs assigning triage scores to ED patients on arrival, using only chief complaint and observation, were statistically comparable to scores assigned utilizing a resource-intense, comprehensive triage system, but clinically significant discrepancies were identified.